Is thyroglobulin detection in fine-needle aspirates useful for the diagnosis of central neck metastatic papillary thyroid cancer?. Issue 12 (31st October 2022) - Song, Yuntao; Wang, Jiaxin; Zhu, Yanli; Xu, Guohui; Wang, Tianxiao; Zhang, Bin
Abstract : Objective: The central neck lymph node (LN) status is important for the treatment strategy of papillary thyroid cancer (PTC), while the diagnosis is difficult. This study aims to evaluate the diagnostic value of fine-needle aspiration (FNA) and its washout thyroglobulin (FNA-Tg) detection in central neck LN metastasis. Methods: Central neck LNs with FNA cytology (FNA-C) and FNA-Tg measurements from a tertiary hospital were included. Tg levels were correlated with histopathological or follow-up results. The diagnostic performance of FNA-C, FNA-Tg, and combining FNA-C and FNA-Tg for detecting LN metastasis was assessed. Results: A total of 132 LNs in the central neck from 129 patients were studied. The median FNA-Tg concentration of 74 metastatic LNs was 552.5 ng/mL, whereas, in 58 benign LNs, the median Tg concentration was 0.1 ng/mL ( P < 0.001). Receiver operating characteristic analysis (area under the curve, 0.861) was used, and a cutoff value of 14.6 ng/mL was obtained. There was no significant increase in the diagnostic accuracy when FNA-Tg was used or combined with FNA-C, compared with FNA-C alone. The size, location of LNs, the presence of the ipsilateral thyroid gland, and Hashimoto's thyroiditis did not affect the incidence of misdiagnosis. Conclusions: FNA-C is the gold standard for evaluating central neck metastasis in PTC patients. Measurement of Tg levels in FNA washout does not improve the diagnostic accuracy any further.